PENERAPAN METODE MULTISENSORI UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA KELAS III DI UPTD SDN 3 KEDOKAN BUNDER WETAN - Umi Mahbubah; Piyantina Rukmini; Dede Hadiansah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigated the effectiveness of a multisensory teaching approach in elementary school science lessons. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, the study spanned three cycles. The primary objectives were to evaluate the impact of the multisensory method on student learning outcomes and classroom engagement. Data were collected through tests and observations. Results indicated a significant improvement in both learning outcomes and student engagement. Specifically, Cycle 1 showed a sufficient level of achievement (score of 32), which progressed to good (64) in Cycle 2 and very good (88) in Cycle 3. Similarly, active student participation increased from 6 students in Cycle 1 to 17 in Cycle 2 and 23 in Cycle 3.